Battery packaging shell, preparation method thereof and secondary battery
By designing aerogel nanocoating in the battery packaging shell, the safety problem of heating up of lithium-ion batteries in extreme environments is solved, the thermal stability and cycling performance of the battery are improved, and the overall performance of the battery is ensured.
Patent Information
- Application Number
- CN202411972513.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
Lithium-ion batteries may experience abnormal heating in extreme environments, resulting in thermal runaway, fire or even explosion, posing safety hazards, and existing high-temperature resistance new materials are costly and difficult to apply.
A battery packaging shell is designed, including a protective layer, barrier layer, aerogel nanocoat and a heat seal layer arranged in sequence from the outside to the inside. The pore size of the aerogel nanocoat is smaller than the particle size of the air molecules, which meets the relationship between specific pore size, porosity, coating area and average thickness to improve thermal insulation performance.
Through the design of the aerogel nanocoating, the thermal stability and cycling performance of the battery are significantly improved, the internal reaction of the battery cell is reduced, the thermal box performance of the battery is improved, and the overall performance of the battery is ensured.
Smart Images

Figure CN119890566A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a battery packaging shell, a preparation method thereof, and a secondary battery. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronics, electric vehicles and other fields due to their high energy density, long cycle life and environmental friendliness. With the continuous development of lithium-ion battery technology and the growing market demand, consumers have put forward higher requirements for the energy density, endurance and fast charging capabilities of lithium-ion batteries. As the demand for energy density of lithium batteries gradually increases, its safety issues are becoming increasingly prominent. Lithium batteries will experience abnormal temperature rise to varying degrees in extreme environments. When the battery temperature reaches a certain level, its internal materials will undergo thermal decomposition to release a large amount of gas and heat, causing the battery temperature to rise rapidly and trigger thermal runaway, resulting in fire or even explosion, posing a safety hazard. The safety issue of batteries under abnormal temperature rise has become an important bottleneck restricting the development of its application fields.
[0003] Existing battery technology, on the one hand, is to develop new battery materials that are resistant to high temperatures and highly inert from the perspective of electrochemical materials, and on the other hand, from the perspective of battery safety management, by clarifying the characteristics of the battery during abnormal heating, corresponding safety management measures and methods are established. As new battery materials are currently expensive and difficult to put into practical application, it is difficult to solve the safety problems that occur when the battery is subjected to abnormal heating.
[0004] Therefore, it is necessary to develop a battery packaging shell that can improve the hot box performance of the battery while ensuring the cycle performance. Summary of the invention
[0005] The purpose of the present invention is to provide a battery packaging shell to improve the hot box performance of the battery while ensuring the cycle performance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A battery packaging shell, comprising a protective layer, a barrier layer, an aerogel nano coating and a heat sealing layer stacked in sequence from the outside to the inside;
[0008] The pore size of the aerogel nanocoating is smaller than the particle size of air molecules, the pore size of the aerogel nanocoating is M, the porosity of the aerogel nanocoating is N, the coating area of the aerogel nanocoating accounts for a ratio of the forward projection area of the barrier layer to S, and the average thickness of the aerogel nanocoating is H;
[0009] Among them, M, N, S and H satisfy the relationship: 0.33≤MS / NH≤0.83.
[0010] Preferably, the aerogel nanocoating comprises aerogel nanoparticles and a binder; the aerogel nanoparticles comprise at least one of silica, alumina, titanium dioxide, magnesium fluoride, calcium fluoride, silicon carbide, boron carbide, boron nitride, titanium nitride, mixed oxides, resorcinol-formaldehyde, melamine-formaldehyde, urethane, polyimide, polymethyl methacrylate, polystyrene, polydicyclopentadiene and carbon nanotubes; the binder comprises at least one of acrylate emulsion, epoxy resin, polyester resin, acrylic resin, polyurethane resin, phenolic resin, polyvinyl chloride resin, aliphatic water-based polyurethane, water-based cellulose resin and polyacrylate.
[0011] Preferably, the pore size of the aerogel nanocoating is 20-50 nm.
[0012] Preferably, the porosity of the aerogel nanocoating is 80-99%.
[0013] Preferably, the average thickness of the aerogel nanocoating is 50-70 μm.
[0014] Preferably, the coating area of the aerogel nanocoating accounts for 80-100% of the forward projection area of the barrier layer.
[0015] Preferably, the heat seal layer comprises at least one of propylene, anhydride-modified polypropylene, polyethylene, ethylene-propylene copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyamide and polyester.
[0016] Preferably, the barrier layer includes at least one of a metal, a polymer or a carbon material, the metal includes at least one of Al, Ni, Ti, Ag, Au, Pt, Fe, Co, Cr, W, Mo, Pb, In, Zn and stainless steel; the polymer includes at least one of polyethylene naphthalate, polyethylene terephthalate and polybutylene terephthalate; the carbon material includes at least one of carbon felt, carbon film, carbon black, acetylene black, fullerene, conductive graphite film and graphene film.
[0017] In addition, the present invention also provides a method for manufacturing a battery packaging shell, comprising the following steps:
[0018] Step S1, spraying the barrier layer on the surface of the protective layer;
[0019] Step S2, after deionized water, a dispersant, a binder and aerogel nanoparticles are uniformly dispersed, a defoaming agent is added and stirred to obtain an aerogel nano coating;
[0020] Step S3, spraying the aerogel nano coating evenly on the inner surface of the barrier layer, then drying and curing, and then coating the heat sealing layer to obtain the packaging shell.
[0021] In addition, the present invention also provides a secondary battery, including a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, and also includes the above-mentioned battery packaging shell.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention provides a battery packaging shell, including a protective layer, a barrier layer, an aerogel nano coating and a heat seal layer stacked in sequence from the outside to the inside; wherein the pore size of the aerogel nano coating is smaller than the particle size of air molecules, so the air flow efficiency on the aerogel nano coating is extremely low, and the specific heat capacity of the aerogel itself is very high, so the heat radiation transfer can be reduced to a minimum, so it has good thermal insulation performance. The aerogel nano coating prevents gaseous and solid heat conduction by virtue of its extremely low volume density and the tortuous path of the nano-grid structure, so that the internal temperature of the battery cell is lower than the box temperature, reducing the occurrence of internal reactions of the battery cell, thereby improving the thermal stability of the battery, and improving the cycle performance and hot box performance of the battery. The present invention improves the thermal stability of the battery by setting the pore size, porosity coating ratio and coating thickness parameters of the aerogel nano coating to meet a specific relationship, and also ensures the comprehensive performance without deteriorating the cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figure is a schematic cross-sectional structure diagram of a battery packaging shell according to an embodiment of the present invention.
[0025] Among them, 1-protective layer; 2-barrier layer; 3-aerogel nano coating; 4-heat sealing layer. DETAILED DESCRIPTION
[0026] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0027] According to the first aspect of the present application, the present application aims to provide a battery packaging shell, comprising a protective layer 1, a barrier layer 2, an aerogel nano coating 3 and a heat sealing layer 4 stacked in sequence from the outside to the inside;
[0028] The pore size of the aerogel nano coating 3 is smaller than the particle size of air molecules, the pore size of the aerogel nano coating 3 is M, the porosity of the aerogel nano coating 3 is N, the coating area of the aerogel nano coating 3 accounts for a ratio of the forward projection area 2 of the barrier layer to S, and the average thickness of the aerogel nano coating 3 is H;
[0029] Wherein, M, N, S and H satisfy the relationship: 0.33≤MS / NH≤0.83, for example, may be 0.33, 0.35, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.83.
[0030] When the relationship satisfies the range, the pore size of the aerogel coating is adjusted to be larger, the porosity is lower, the coating is thinner, and the coating area is moderately reduced. Comprehensive adjustment in this direction is more conducive to the improvement of cycle performance.
[0031] Among them, the pore size of the aerogel nano coating 3 is smaller than the particle size of air molecules. The heat seal layer 4 can prevent the corrosion of the electrolyte and prevent the electrolyte from being stored in the pores of the aerogel, acting as a conductor. When the battery cell is placed in a high-temperature box, the aerogel nano coating, with its extremely low volume density and the tortuous path of the nano-grid structure, prevents gaseous and solid heat conduction, making the internal temperature of the battery cell lower than the box temperature, reducing the occurrence of internal reactions of the battery cell, thereby improving the thermal stability of the battery and improving the battery hot box performance. When the pore size of the aerogel nano coating is smaller than the particle size of air molecules, the air flow efficiency on the aerogel is extremely low. In addition, the specific heat capacity of the aerogel itself is very high, so the heat radiation transfer can be minimized, and it has good thermal insulation performance.
[0032] In some embodiments, the aerogel nano coating 3 includes aerogel nanoparticles and a binder; the aerogel nanoparticles include at least one of silicon dioxide, aluminum oxide, titanium dioxide, magnesium fluoride, calcium fluoride, silicon carbide, boron carbide, boron nitride, titanium nitride, mixed oxides, resorcinol-formaldehyde, melamine-formaldehyde, urethane, polyimide, polymethyl methacrylate, polystyrene, polydicyclopentadiene and carbon nanotubes; the binder includes at least one of acrylate emulsion, epoxy resin, polyester resin, acrylic resin, polyurethane resin, phenolic resin, polyvinyl chloride resin, aliphatic water-based polyurethane, water-based cellulose resin and polyacrylate. Aerogel is a highly dispersed solid material in which colloidal particles or polymer molecules are mutually aggregated to form a nanoporous network structure, and the pores are filled with a gaseous dispersion medium. It has the characteristics of extremely large specific surface area, high specific strength, low density, high light transmittance, extremely low thermal conductivity and high porosity.
[0033] In some embodiments, the pore size of the aerogel nano coating 3 is 20-50nm, for example, it can be 20nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm. The particle size of air molecules is about 70nm, and the pore size of the aerogel nano coating needs to be set smaller than that of air molecules to reduce the efficiency of air flow on the aerogel, thereby improving the thermal insulation performance. When the pore size of the aerogel nano coating is too small, the solid thermal conductivity will be too low, and the internal heat of the battery cell during use cannot be transferred out. When the pore size of the aerogel nano coating is too large, the air flow efficiency on the aerogel will become higher, which will deteriorate the thermal insulation performance of the aerogel nano coating.
[0034] In some embodiments, the porosity of the aerogel nano coating 3 is 80-99%, for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 99%. When the porosity of the aerogel nano coating is too low, the thermal conductivity will increase, thereby reducing the thermal insulation performance.
[0035] In some embodiments, the average thickness of the aerogel nano coating 3 is 50-70 μm, for example, 50 μm, 52 μm, 54 μm, 56 μm, 58 μm, 59 μm, 60 μm, 62 μm, 64 μm, 66 μm, 68 μm, 70 μm. When the average thickness of the aerogel nano coating is too small, it will affect the uniformity of its coating, causing the coating to be easily damaged and affecting the thermal insulation effect. When the average thickness of the aerogel nano coating is too large, it will increase the thickness of the battery cell and lose energy density.
[0036] In some embodiments, the coating area of the aerogel nano coating 3 accounts for 80-100% of the forward projection area of the barrier layer 2, for example, it can be 80%, 85%, 90%, 95%, 100%. Aerogel has ultra-fine honeycomb pore size and porous structure. When the coating area accounts for 100% of the forward projection area of the barrier layer, the thermal stability is optimal. When the coating area of the aerogel nano coating is too small, it will cause too much temperature to be transferred from the uncoated area to the inside of the battery cell, affecting the thermal insulation effect.
[0037] In some embodiments, the protective layer 1 includes at least one of a nylon layer and a composite layer of PET and nylon.
[0038] In some embodiments, the barrier layer 2 includes at least one of a metal, a polymer or a carbon material, the metal including at least one of Al, Ni, Ti, Ag, Au, Pt, Fe, Co, Cr, W, Mo, Pb, In, Zn and stainless steel; the polymer includes at least one of polyethylene naphthalate, polyethylene terephthalate and polybutylene terephthalate; the carbon material includes at least one of carbon felt, carbon film, carbon black, acetylene black, fullerene, conductive graphite film and graphene film.
[0039] In some embodiments, the heat seal layer 4 includes at least one of propylene, anhydride-modified polypropylene, polyethylene, ethylene-propylene copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyamide, and polyester.
[0040] According to a second aspect of the present application, the present application provides a method for preparing a packaging shell, comprising the following steps:
[0041] Step S1, spraying the barrier layer on the surface of the protective layer;
[0042] Step S2, after deionized water, a dispersant, a binder and aerogel nanoparticles are uniformly dispersed, a defoaming agent is added and stirred to obtain an aerogel nano coating;
[0043] Step S3, spraying the aerogel nano coating evenly on the inner surface of the barrier layer, then drying and curing, and then coating the heat sealing layer to obtain the packaging shell.
[0044] In some embodiments, in step S2, the defoaming agent is any one of metal soaps, mineral oils, fatty acids and their salts, polyethers, organosilicon compounds, polyethylene glycol fatty acid esters, polyurethanes and polyamides.
[0045] According to the third aspect of the present application, the present application also provides a secondary battery, including a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, and also includes the above-mentioned battery packaging shell.
[0046] The current collector can be any material suitable for use as a positive electrode current collector for lithium-ion batteries in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to aluminum foil.
[0047] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be various materials in the art that are suitable for use as a negative electrode current collector for lithium-ion batteries. For example, the negative electrode current collector may include but is not limited to metal foil, and more specifically may include but is not limited to copper foil.
[0048] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0049] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0050] Example 1
[0051] (1) Preparation of positive electrode
[0052] The positive electrode material lithium cobalt oxide, mixed conductive agent and binder polyvinylidene fluoride (PVDF) were fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 98:1.0:1.0, and then coated on Al foil. After drying, rolling and slitting, a positive electrode sheet was obtained.
[0053] (2) Preparation of negative electrode
[0054] Graphite, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a deionized water solvent system at a mass ratio of 97.8:1.1:1.1, and then coated on a Cu foil. After drying, rolling, and slitting, a negative electrode sheet was obtained.
[0055] (3) Preparation of diaphragm
[0056] The PE surface is coated with a ceramic mixture as an isolation membrane.
[0057] (4) Preparation of electrolyte
[0058] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 25:25:15:31:4, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of the lithium battery.
[0059] (5) Preparation of packaging shell
[0060] Step S1, spraying the barrier layer on the surface of the protective layer;
[0061] Step S2, deionized water and dispersant are added into aliphatic waterborne polyurethane in sequence and stirred and dispersed evenly, then weighed silica aerogel is slowly added and dispersed at high speed for 30 minutes, and finally weighed silicone defoamer polydimethylsiloxane is added and stirred at low speed for 5 minutes to prepare aerogel nano coating;
[0062] Step S3, spraying the aerogel nano coating evenly on the inner surface of the barrier layer, then drying and curing, and then coating the heat sealing layer to obtain the packaging shell.
[0063] Among them, the particle size of the aerogel nanocoating is 30nm, the porosity is 95%, the average thickness is 60μm, and the coating area accounts for 100%.
[0064] (6) Preparation of batteries
[0065] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, and the electrolyte is injected into the packaging shell and packaged to finally obtain a lithium-ion battery.
[0066] Among them, the preparation methods of Examples 2-8 and Comparative Examples 2-7 are the same as the preparation method of Example 1, except for the aerogel nanocoating parameters. The battery packaging shell in Comparative Example 1 does not contain aerogel nanocoating, as shown in Table 1 below.
[0067] Table 1
[0068]
[0069]
[0070] Test method:
[0071] (1) Cycle performance test: The prepared lithium-ion battery was charged at 3.5C CC to 4.25V, CV to 2.8C, CC to 4.35V, CV to 1.8C, CC to 4.5V, CV to 0.02C. The cycle performance of the battery was tested for 800 cycles.
[0072] (2) Hot box performance test: The prepared lithium-ion battery is charged, 0.5C CC to 4.53V, CV to0.02C, and the charged battery is placed in a thermal shock test box (hanging test), and heated by convection or circulating hot air at a starting temperature of 25±3℃. The oven temperature is raised at a rate of 5±2℃ / min to a temperature at which the battery cell does not catch fire or explode, and the temperature is maintained for 60 minutes before stopping, indicating that the test has passed.
[0073] The test results are shown in Table 2.
[0074] Table 2
[0075]
[0076]
[0077] From the data comparison of Examples 1-8 and Comparative Examples 1-7 in Table 1, it can be seen that the battery packaging shell provided by the present application makes the internal temperature of the battery cell lower than the box temperature, reduces the occurrence of internal reactions of the battery cell, thereby improving the thermal stability of the battery and improving the hot box performance of the battery. When the battery packaging shell of Comparative Example 1 does not contain an aerogel nanocoating, the thermal stability of the battery cell is poor, thereby deteriorating the cycle retention rate and hot box performance of the battery. By adjusting the MS / (NH) value to 0.33-0.83, that is, the larger the pore size of the aerogel coating, the lower the pores, the appropriate thinning of the coating, and the appropriate reduction in the coating area, the comprehensive adjustment in this direction is more conducive to not deteriorating the cycle performance while ensuring the improvement of the overall performance.
[0078] From the data comparison of Examples 1-3 and Comparative Example 2, it can be seen that the cycle performance of the battery improves as the porosity of the aerogel nanocoating decreases, and the hot box performance decreases as the porosity of the aerogel nanocoating decreases, but when the porosity is too low, both the cycle performance and the hot box performance of the battery will deteriorate.
[0079] From the comparison of the data of Example 2 and Comparative Example 3, it can be seen that when the coating area of the aerogel nanocoating is smaller than the set range, the effective insulation area is reduced, resulting in poor performance of the hot box.
[0080] From the data comparison of Examples 4-6 and Comparative Examples 4-5, it can be seen that the cycle performance of the battery improves with the increase of the pore size of the aerogel nanocoating, and the hot box performance decreases with the increase of the pore size of the aerogel nanocoating. When the pore size of the aerogel nanocoating is smaller than the set range, the solid thermal conductivity will be too low, the internal heat of the battery cell during use cannot be transferred out, and the cycle performance will deteriorate; when the pore size of the aerogel nanocoating is larger than the set range, the air flow efficiency on the aerogel will increase, the thermal insulation performance of the aerogel nanocoating will deteriorate, and the hot box will deteriorate.
[0081] From the data comparison of Examples 1, 7-8 and Comparative Examples 6-7, it can be seen that when the average thickness of the aerogel nanocoating is less than the set range, the coating thickness may be uneven, resulting in a deterioration of the hot box; when the average thickness of the aerogel nanocoating is greater than the set range, the thickness of the battery cell increases, the heat dissipation deteriorates, and the cycle performance deteriorates.
[0082] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A battery packaging shell, characterized in that: It includes a protective layer, a barrier layer, an aerogel nano coating and a heat sealing layer which are sequentially stacked from the outside to the inside; The pore size of the aerogel nanocoating is smaller than the particle size of air molecules, the pore size of the aerogel nanocoating is M, the porosity of the aerogel nanocoating is N, the coating area of the aerogel nanocoating accounts for a ratio of the forward projection area of the barrier layer to S, and the average thickness of the aerogel nanocoating is H; Among them, M, N, S and H satisfy the relationship: 0.33≤MS / NH≤0.
83.
2. The battery packaging shell according to claim 1, characterized in that: The aerogel nano coating comprises aerogel nanoparticles and a binder; The aerogel nanoparticles include at least one of silicon dioxide, aluminum oxide, titanium dioxide, magnesium fluoride, calcium fluoride, silicon carbide, boron carbide, boron nitride, titanium nitride, mixed oxides, resorcinol-formaldehyde, melamine-formaldehyde, urethane, polyimide, polymethyl methacrylate, polystyrene, polydicyclopentadiene and carbon nanotubes; The binder includes at least one of acrylate emulsion, epoxy resin, polyester resin, acrylic resin, polyurethane resin, phenolic resin, polyvinyl chloride resin, aliphatic waterborne polyurethane, waterborne cellulose resin and polyacrylate.
3. The battery packaging shell according to claim 1, characterized in that: The pore size of the aerogel nano coating is 20-50 nm.
4. The battery packaging shell according to claim 1, characterized in that: The porosity of the aerogel nano coating is 80-99%.
5. The battery packaging shell according to claim 1, characterized in that: The average thickness of the aerogel nano coating is 50-70 μm.
6. The battery packaging shell according to claim 1, characterized in that: The coating area of the aerogel nano coating accounts for 80-100% of the forward projection area of the barrier layer.
7. The battery packaging shell according to claim 1, characterized in that: The heat seal layer includes at least one of propylene, anhydride-modified polypropylene, polyethylene, ethylene-propylene copolymer, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyamide and polyester.
8. The battery packaging shell according to claim 1, characterized in that: The barrier layer includes at least one of a metal, a polymer or a carbon material, the metal includes at least one of Al, Ni, Ti, Ag, Au, Pt, Fe, Co, Cr, W, Mo, Pb, In, Zn and stainless steel; the polymer includes at least one of polyethylene naphthalate, polyethylene terephthalate and polybutylene terephthalate; the carbon material includes at least one of carbon felt, carbon film, carbon black, acetylene black, fullerene, conductive graphite film and graphene film.
9. A method for preparing a battery packaging shell according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, spraying the barrier layer on the surface of the protective layer; Step S2, after deionized water, a dispersant, a binder and aerogel nanoparticles are uniformly dispersed, a defoaming agent is added and stirred to obtain an aerogel nano coating; Step S3, spraying the aerogel nano coating evenly on the inner surface of the barrier layer, then drying and curing, and then coating the heat sealing layer to obtain the packaging shell.
10. A secondary battery, characterized in that: A battery packaging shell comprising any one of claims 1-8.
Citation Information
Cited By
High-temperature-resistant high-barrier composite film and preparation method thereof
CN120503490A
High-temperature-resistant high-barrier composite film and preparation method thereof
CN120503490B